Perioperative Respiratory Disorders in Spinal Cord Compressions - Yu. A. Churlyaev; K. V. Lukashyov; V. Ya. Martynenkov (Общая реаниматология)
Objective: to study external respiration in patients with damage to the spinal cord of various genesis (compression myelopathy) at the lower cervical and thoracic levels depending on the degree of its conduction disturbances in order to select an analgesic mode as part of postoperative intensive care. Subjects and methods. Before and 1—3, and 5—7 days after surgery, 30 patients with spinal cord damage at the lower cervical and thoracic levels were examined, by determining external respiratory function (vital capacity (VC), forced VC (FVC), forced expiratory volume in 1 second (FEV1), Gaenslar index, average forced expiratory volume velocity (AFEVV25—75%); by performing cliniconeuro-logical and neurophysiological (electromyography (EMG), needle EMG, and somatosensory evoked potentials (SSEP)) studies; according to these indices, the gender- and age-matched patients were divided into 2 groups: 1) those who had complete spinal cord conduction disturbances and 2) those who had incomplete one. According to the postoperative analgesia mode, the following groups were identified: A) conventional systemic administration of opioid analgesics (promedol); B) prolonged epidural blockade with anecaine solution at the Th2—3 level. External respiration was studied after disconnecting the patient from a respirator before and after analgesia. A control group comprised 18 apparently healthy volunteers. Results. Before surgery, restrictive respiratory disorders were observed in Group 1 and they were absent in Group 2. In the postoperative period, all the patients were found to have mixed disorders that were most pronounced in Group 1. In Group A, the postoperative duration of artificial ventilation was significantly greater and it was 160.0±21.0 minutes whereas it was 90.0±25.0 minutes in Group 2 (p<0.05). With postoperative analgesia, Group A showed 1.7—2.2-fold decreases in VC, FVC, FEV1, and AFEVV25—75% (p<0.05) as compared with the baseline levels. There was a significant reduction in PaO2 to 85.5±2.3 mm Hg and an increase in PaCO2 to 41.5±1.4 mm Hg as compared with Group B. In this group, VC, FVC, FEV1, AFEVV25—75% postoperatively decreased by 1.1—1.3 time (p<0.05), Pa02=100±3.3 mm Hg and PaCO2=35.7±1.7 mm. Conclusion. Following surgery, neurogenic respiratory disorders progress in patients with varying damage to the spinal cord (compression myelopathy) and to a greater extent in those with its complete conduction disturbances. The postoperative use of prolonged epidural blockade versus opioid analgesics promotes early activation, patients’ adaptation to spontaneous respiration and prevention of lung complications. Key words: spinal cord damage, neurogenic respiratory failure, postoperative period.